IMPLEMENTASI SISTEM INFORMASI PARTAI POLITIK (SIPOL) PADA TAHAPAN VERIFIKASI PARTAI POLITIK CALON PESERTA PEMILIHAN UMUM TAHUN 2024 DI KOMISI PEMILIHAN UMUM KABUPATEN MUARA ENIM - Alfarabi, Ahmad; Warganegara, Arizka; Maryanah, Tabah (MEDIOVA: Journal of Islamic Media Studies, 2023)
The political party information system (SIPOL) is a special application used by the Indonesian KPU to verify data on political parties participating in elections, which also aims to help political parties manage and update data on administrators and membership at every level. The theory used in this research is 12 principles of the use of information system technology in elections. The research method used is direct observation, documentation and literature. The aim of this study is for evaluating the KPU's development and improvements to the SIPOL application. The research analysis uses inductive qualitative analysis, namely research analysis based on the data obtained and then supported by reference materials. The results in this study are that SIPOL is effective in assisting KPU performance in verifying political party membership data. As well as being efficient, transparent, easy to use, flexible, and accurate in helping Political Parties manage and update Management and Membership data at every level. The design of SIPOL is not only intended to provide services to political parties to fill in management and membership data and assist the KPU in conducting administrative and factual verification, but also to encourage accountability, transparency, and public participation in controlling the work of the KPU in conducting the verification process of political parties.